Exosomes Derived From Human Gingival Mesenchymal Stem Cells Attenuate the Inflammatory Response in Periodontal Ligament Stem Cells - Sun, Jiayao; Wang, Zhiguo; Liu, Peng; Hu, Yingzhe; Li, Tingting; Yang, Jianbo; Gao, Pengyu; Xu, Quanchen (Frontiers in Chemistry, 2022)
Periodontitis is a chronic infectious disease characterized by periodontal tissue inflammation and alveolar bone destruction. Periodontal ligament stem cells (PDLSCs) are regarded as an ideal seed cell for restoring periodontal tissue defects because of their ability to generate cementum/PDL-like tissue and alveolar bone. However, PDLSCs in the inflammatory environment show significantly attenuated regenerative potential. Exosomes derived from human gingival mesenchymal stem cells (GMSC-Exo) have been reported to have anti‐inflammatory and immunosuppressive properties. In this study, we investigated the effects of GMSC-Exo on the inflammatory response of PDLSCs induced by lipopolysaccharide (LPS). LPS was used to simulate the inflammatory microenvironment of periodontitis in vitro. GMSC-Exo was extracted from the culture supernatant of GMSCs by ultracentrifugation. We found that GMSC-Exo attenuated the inflammatory response of PDLSCs induced by LPS. Furthermore, compared to treatment with LPS, treatment with GMSC-Exo attenuated the expression of NF-κB signaling and Wnt5a in LPS-induced PDLSCs. This study aimed to explore the effects of GMSC-Exo on the inflammatory response of PDLSCs in an inflammatory microenvironment in order to restore the regenerative potential of PDLSCs, which help to promote periodontal tissue regeneration in patients with periodontitis.